Losing touch with mother seed: Insights from action research with small-scale farmers in Tamil Nadu, India - Afla C P; Anna KJ Steffy; Atul Raman; Devisha Sasidevan; Dhanya Kolathur; Ghurshida Jabeen; Sowmya Balasubramaniam; Sunil Damodaran Santha (Journal of Political Ecology, 2024)
The article showcases the nature of climate colonialism by examining the transitions in heirloom seed conservation practices in the context of climate change. Insights for this article are drawn from an action research project implemented among heirloom seed keepers and small-scale farmers in Tamil Nadu, India. Local knowledge systems and indigenous seed conservation practices play a crucial role in strengthening the resilience of small-scale farmers to climate variability and extreme weather events. Throughout India, traditional seed keepers have voluntarily taken up the responsibility of collecting and conserving native and heirloom seeds for future generations. These practices also ensure that sustainable farming practices are adopted. However, the modernization and commercialization of agriculture since the colonial and post-independence periods have displaced several such practices, paving the way for the mass consumption of hybrid seed varieties and chemical fertilizers and pesticides. With the advent of climate change as both global discourse and locally experienced phenomena, yet another layer of dispossession and the cheapening of nature has occurred. The key argument of this article is that climate change adaptation has become a new commodity frontier, dispossessing and alienating small-scale producers.